Approximation of substantive criminal law in the EU The way forward - de Biolley, Serge (European Studies, 2013)
This book dedicated to the substantive criminal law in the EU put the Libson Treaty under scrutiny. It evaluates the changes introduced by this new Treaty and their impact, before reflecting on future prospects.